Bortezomib, melphalan, prednisone (VMP) versus melphalan, prednisone, thalidomide (MPT) in elderly newly diagnosed multiple myeloma patients: A retrospective case‐matched study. Issue 4 (5th February 2014) - Morabito, Fortunato; Bringhen, Sara; Larocca, Alessandra; Wijermans, Pierre; Victoria Mateos, Maria; Gimsing, Peter; Mazzone, Carla; Gottardi, Daniela; Omedè, Paola; Zweegman, Sonja; José Lahuerta, Juan; Zambello, Renato; et al.
<x xml:space="preserve">Abstract</x> Novel agents in combination with melphalan and prednisone (MP) significantly improved progression‐free survival (PFS) and overall survival (OS) in multiple myeloma (MM). Randomized trials comparing MP plus bortezomib (VMP) versus MP plus thalidomide (MPT) are lacking. Nine hundred and fifty‐six elderly (>65 years) newly diagnosed MM patients from six European randomized trials were retrospectively analyzed and matched for age, albumin, and beta2‐microglobulin at diagnosis, 296 patients were selected from the VMP groups, and 294 from MPT. Complete response rate was 21% in the VMP patients and 13% in the MPT patients (P = 0.007). After a median follow‐up of 34 months (range, 1–92), VMP significantly prolonged both PFS (median 32.5 vs. 22.9 months, HR 0.65; 95% CI 0.52–0.82; P < 0.001) and OS (median 79.7 vs. 45.1 months, HR 0.44; 95% CI 0.32–0.59; P < 0.001) in comparison with MPT. The benefit in terms of OS of the VMP group was quite similar among patients with different risk factors defined by sex, ISS, ECOG performance status, or serum creatinine but not among patients ≥75 years. Multivariate analysis confirmed that VMP was an independent predictor of longer PFS and OS. In a control‐case matched analysis, PFS and OS were prolonged in patients who received VMP in comparison with those treated with MPT. Am. J. Hematol. 89:355–362, 2014. © 2013 Wiley Periodicals, Inc.